His Majesty the Regent of Pahang appointed Royal Patron of UMP Volunteers - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PEKAN, 17 February 2022 - His Majesty the Regent of Pahang Tengku Mahkota Tengku Hasanal Ibrahim Alam Shah Ibni Al-Sultan Abdullah Ri’ayatuddin Al-Mustafa Billah Shah was appointed as the Royal Patron for the Universiti Malaysia Pahang (UMP) Volunteers.